Wood defects categories - Mohd Suhaili, Mohd Aniz Anizar (2007)
Wood is and will still become primary source in their human daily life. In past years, wood is only used as firewood, as an arms, make the material built and sources of food for certain animal. Now, wood give the main contribution in the many industries that utilize wood resources. As we know, the good wood can give the best quality product, which we produced. Sometimes, the wood defects can give big problem to the all wood product producer because wood defects sometimes can be prevented and sometime not. The type of wood defects that we face with is natural wood defects, seasoning wood defects and wood defects during machining. So, the best way to get the quality wood is to use special drying schedule and to person who handle the machine should be more careful. It is very important to get the high value of wood in the market. It is because, there are difficult to get the good log in the short time.